The effect of endurance, resistance and concurrent training on respiratory capacity of cystic fibrosis patients - Ashkan Sohrabi; Samaneh Ebrahimi; Ehsan Arabzadeh; Mandana Gholami (Advanced Exercise and Health Science)
Cystic fibrosis (CF) is a multisystem disease that may affect organ systems, including the respiratory system. Exercise training provides multiple benefits for people with CF. The purpose of this study was to determine the effects of three exercise-training programs on respiratory capacity and pulmonary function in patients with CF. Sixty CF patients (age 8–15 years, body mass index or BMI > 16 kg/m2) were randomly allocated to three experimental groups including: Endurance training (ET, n = 15), Resistance training (RT, n = 15), Concurrent Training (CT, n = 14) and control (C, n = 16). Trainings groups completed a 10-week moderate exercise programs (endurance, resistance and concurrent modality). Spirometry was performed both prior to randomization and following the intervention to assess first second of forced expiration (FEV1), forced vital capacity (FVC) and FEV1/FVC ratio. Health-related quality of life (HRQoL) was assessed using the adolescent/adult version of the CF Questionnaire. The results show that 10-weeks of supervised ET, RT and CT improved FEV1, FVC, FEV1/FVC (%), peak expiratory flow (PEF) (l/s), forced mid-expiratory flow (FEF) 25–75 % (l/s), maximal voluntary ventilation (MVV) dimension, and HRQoL (p < 0.05). In addition, in the three exercise groups, a significant improvement in all variables at post-test was observed when compared to pre-test (p < 0.05). In CF patients, performing controlled endurance, resistance and combined exercises improved functional and respiratory parameters. However, it seems that combined exercises had a greater effect on these variables than resistance and endurance exercises alone.